Strengthening Institutional Oversight of Transfer Pricing in Indonesia: Towards Legal Certainty Tax Governance - Ariska Cesar Divian Candra Kusuma (Journal of Innovative and Creativity, 2025)
This study examines the institutional oversight of transfer pricing in Indonesia and Malaysia from the perspective of international tax law, focusing on regulatory harmonization, administrative structure, and dispute prevention mechanisms. The issue of transfer pricing has evolved beyond a technical tax matter into one of fiscal justice and national sovereignty amid globalization and the increasing complexity of multinational enterprises (MNEs). While both Indonesia and Malaysia have aligned their regulatory frameworks with the OECD Transfer Pricing Guidelines and the BEPS Action Plan, their institutional capacities differ significantly. Malaysia has consolidated its transfer pricing governance through the establishment of a dedicated Transfer Pricing Division under the Inland Revenue Board of Malaysia (IRBM), supported by comprehensive instruments such as the Income Tax (Transfer Pricing) Rules 2012/2023, Transfer Pricing Guidelines 2017/2024, and APA and MAP Guidelines. In contrast, Indonesia’s oversight remains fragmented across multiple directorates within the Directorate General of Taxes (DGT), leading to inconsistent interpretations, weak coordination, and reduced administrative efficiency. This institutional fragmentation undermines legal certainty, facilitates profit shifting, and contributes to both horizontal and vertical tax inequities. The study argues for the establishment of a dedicated transfer pricing division within the DGT to strengthen institutional capacity, enhance coordination with the Directorate General of Customs and Excise, and improve the utilization of risk-based audits and dispute prevention mechanisms. By adopting Malaysia’s integrated institutional model, Indonesia can align more effectively with OECD standards, promote fiscal fairness, legal certainty and reinforce national tax sovereignty within a globally interconnected economy.